Internalisasi Karakter Gotong Royong Dalam Pembelajaran PKN Di SD - Muhammad Fauzan Muttaqin; Hadi Rohyana (Jurnal Elementaria Edukasia, 2023)
There is a lot of news in the mass media about deviant behavior among students, including acts of bullying, physical violence, discriminating against friends, and so on. At SD FULLDAY DAQU SCHOOL, the school has tried to counteract these things by internalizing the character values of mutual cooperation in the school environment and in learning. This study aims to analyze the application of mutual cooperation character values that are internalized into civics education learning. The research method uses a descriptive qualitative approach. The subjects of this study were headmaster, teachers and students of low class I, II, III. This study uses interviews, observation, and documentation in data collection. The analysis technique uses triangulation of data sources. The results showed that students were trained to give alms and pray for each other which were contained in the daqu method, cooperation, respect, and solidarity. In practice, teachers use ICT, PBL, cooperative, and contextual learning models. The learning methods used are lectures, demonstrations, singing, discussions, and class outings as well as the learning strategies used are contextual, inquiry and expository.